Dissolved organic metabolite extraction from high‐salt media. (10th August 2022) - Holderman, Nicole R.; Ferrer‐González, Frank X.; Glushka, John; Moran, Mary Ann; Edison, Arthur S.
Abstract : We describe considerations and strategies for developing a nuclear magnetic resonance (NMR) sample preparation method to extract low molecular weight metabolites from high‐salt spent media in a model coculture system of phytoplankton and marine bacteria. Phytoplankton perform half the carbon fixation and oxygen generation on Earth. A substantial fraction of fixed carbon becomes part of a metabolite pool of small molecules known as dissolved organic matter (DOM), which are taken up by marine bacteria proximate to phytoplankton. There is an urgent need to elucidate these metabolic exchanges due to widespread anthropogenic transformations on the chemical, phenotypic, and species composition of seawater. These changes are increasing water temperature and the amount of CO2 absorbed by the ocean at energetic costs to marine microorganisms. Little is known about the metabolite‐mediated, structured interactions occurring between phytoplankton and associated marine bacteria, in part because of challenges in studying high‐salt solutions on various analytical platforms. NMR analysis is problematic due to the high‐salt content of both natural seawater and culture media for marine microbes. High‐salt concentration degrades the performance of the radio frequency coil, reduces the efficiency of some pulse sequences, limits signal‐to‐noise, and prolongs experimental time. The method described herein can reproducibly extract low molecular weight DOM from small‐volume, high‐salt cultures. It is a promising tool for elucidating metabolic flux between marine microorganisms and facilitates genetic screens of mutant microorganisms. Abstract : We describe an analytical approach for extracting low molecular weight (LMW) metabolites from high‐salt exudates in a model coculture system of phytoplankton and associated marine bacteria. These microorganisms exchange metabolites that are important to carbon cycling and numerous other global biogeochemical cycles. The optimized protocol employs lyophilization, mechanical homogenization, and reconstitution in DMSO‐d6, successfully isolating LMW metabolites while diminishing the effects of salt on the NMR measurements.